Determination of Caffeine, Theobromine, and Theophylline by HPLC-DAD in Beverages Commonly Consumed in Lima, Peru - Karolinhe A. Gonzales-Yépez; Jorge Luis Vilela; Oscar Reátegui (International Journal of Food Science)
The purpose of this study was to determine the content of caffeine, theobromine, and theophylline by high-performance liquid chromatography with diode-array detection (HPLC-DAD) in beverages commonly consumed in Lima, Peru. The samples were divided into 6 groups (herbal teas, coffee powder, chocolate milks, soft drinks, sports drinks, and energy drinks) which included the five most commonly consumed beverages of the different groups. Caffeine was mainly identified in the soft drink and energy drink groups, with the latter having a more significant value (10.38±0.01 vs. 95.50±3.48 mg/L, respectively). In herbal teas, caffeine showed the highest content (0.47±0.01 to 4.91±0.05 mg/L), despite theophylline being a characteristic compound of tea leaves. Sports drinks presented very low caffeine levels (0.03±0.01 to 0.05±0.01 mg/L), and theobromine (0.48±0.01 to 6.00±0.02) was also identified. Caffeine (4.09±0.01 to 5.70±0.01 mg/L) and theobromine (1.70±0.01 to 12.24±0.01 mg/L) were found in the five commercial brands of chocolate milk evaluated. Moreover, the group of coffee powder samples had the highest level of caffeine content (49.25±0.24 to 964.40±4.93 mg/100 g). The results obtained in this study provide reliable information on the composition and quantification of methylxanthines in the beverages most consumed in Lima and impact consumer knowledge.